(3GdehLR GdMGhj dJMQjQ GdaJGhjs - (3GdCSOj, GdMdj, CHh GdYHGS, LeGd GdOjf, CMeO Hf eMeO Hf agO, J (B841(3g`s ((3fUQ Gddg Hf HQbY Hf JQcj Hf UGdM GdWQajs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO abO GSJNQJ Gddg SHMGfg hJYGdi hYedJ gPG GdeNJUQ hSejJg HGdehLR GdMGhj dJMQjQ GdaJGhjs
(3BNQgG (B:s
(3hdh cGfJ TGI LGR CMOgG hEYWGDg (B... (3hddabjQ(B... (3Je GdcJGH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U (B226s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B604s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis